Empowering Posbindu Cadres through Digital Health Training: Optimizing the ASIK Application in Kendal Regency - Arief Azhari Ilyas; Zefan Adiputra Golo; Ibon Fajar Saputra (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2026)
Digital transformation in the health sector requires the optimization of health application utilization by community health cadres as the frontline providers of community-based services. However, limited digital literacy and technical skills remain significant barriers to the effective use of the Sehat Indonesiaku Application (ASIK) in Integrated Non-Communicable Disease Posts (Posbindu PTM) in rural areas. This community service activity aimed to optimize the role of Posbindu cadres in utilizing ASIK to support more efficient, accurate, and integrated recording and reporting of non-communicable disease (NCD) data in Sumberejo Village, Kaliwungu District, Kendal Regency. The implementation method consisted of preparation, a knowledge pre-test, socialization of the ASIK application, demonstrations and hands-on practice with intensive mentoring, and evaluation through a post-test and discussion. The activity was conducted on July 23, 2025, involving 20 Posbindu PTM cadres. The results demonstrated a significant improvement in cadres’ knowledge and skills in using ASIK, as indicated by higher post-test scores compared to pre-test results and the successful installation and operation of basic application features by all participants for NCD data recording. This activity confirms that practice-based socialization and mentoring are effective in strengthening Posbindu cadres’ capacity and supporting the implementation of digital health recording systems in rural areas.